Pemberdayaan Masyarakat Melalui Pengolahan Sampah Organik untuk Menghasilkan Pakan Ternak di Desa Situraja Utara Sumedang - Azhar Affandi; Eddy Jusuf; Asep Dedy Sutrisno; Dindin Abdurohim BS; Win Hendrawan (Bandung Conference Series: Economics Studies, 2024)
Abstract. Waste management problems are still in the spotlight, one of which is at the waste management site in Situraja Utara Village, Situraja District, Sumedang Regency. Among others, waste is mixed and has not been sorted, people's behavior of burning waste, and lack of garbage cans. The community service team empowers the community in terms of waste management, especially organic waste. Social and economic approaches are carried out in order to shape the motivation and environmental awareness of the community. This activity aims to encourage the manufacture of superior village products, through processing waste into fish or livestock feed with bioconversion methods. The results of activities are in the form of assistance in making products to setting marketing targets. The potential of waste management site in Situraja Utara village to produce economically valuable products must be encouraged to be sustainable. Abstrak. Permasalahan pengelolaan sampah masih menjadi sorotan, salah satunya di Tempat Pengelolaan Sampah (TPS) di Desa Situraja Utara Kecamatan Situraja Kabupaten Sumedang. Antara lain sampah tercampur dan belum dilakukan pemilahan, perilaku masyarakat kebiasaan membakar sampah, dan kurangnya tong sampah. Tim pengabdian masyarakat melakukan pemberdayaan masyarakat salam pengelolaan sampah khususnya sampah organik. Pendekatan secara sosial dan ekonomi dilakukan agar membentuk motivasi dan kesadaran lingkungan masyarakat. Kegiatan ini bertujuan mendorong pembuatan produk unggulan desa, melalui pengolahan sampah menjadi pakan ikan atau ternak dengan metode biokonversi. Hasil kegiatan berupa pendampingan pembuatan produk sampai dengan menetapkan target pemasaran. Potensi TPS Situraja Utara untuk menghasilkan produk bernilai ekonomis harus didorong agar berkelanjutan.